2013
DOI: 10.1073/pnas.1309820110
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of copper to superoxide dismutase involves scaffolding by membranes

Abstract: Significance What are the odds that a 1,000 Å 3 -sized metal-binding site will find its cargo parsing a volume of 30 trillion Å 3 by a random 3D diffusional process? Establishing a unique paradigm in the field of copper biology, we show that cells use a stunningly simple method to beat these odds by reducing the dimensionality of the problem through exploitation of cellular membranes as scaffolding components. We demonstrate that the copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…Therefore, the only way to transport the metal to another protein is via direct protein-protein interactions. Whereas CCS has been shown to interact with membranes and to receive Cu directly from Ctr1 (Pope et al 2013), Ctr1-Atox1 interactions have not been described except for the yeast protein pair (Xiao and Wedd 2002). Thus, it is a possibility that Cu delivery to Atox1 goes via CCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the only way to transport the metal to another protein is via direct protein-protein interactions. Whereas CCS has been shown to interact with membranes and to receive Cu directly from Ctr1 (Pope et al 2013), Ctr1-Atox1 interactions have not been described except for the yeast protein pair (Xiao and Wedd 2002). Thus, it is a possibility that Cu delivery to Atox1 goes via CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Since both Atox1 and CCS possess the capacity to interact with lipid bilayers, membrane scaffolding may facilitate the interaction between Ctr1 and the chaperones (Pope et al 2013). In yeast, Ctr1 has a cytosolic C-terminal domain that was shown to interact with the yeast Atx1 chaperone and deliver Cu (Xiao and Wedd 2002).…”
mentioning
confidence: 99%
“…It has been suggested that virtually all cellular Cu is tightly bound, and intracellular Cu trafficking is carried out by Cu chaperones to different cellular compartments, i.e, CCS to superoxide dismutase in the cytoplasm [12], Cox17 to mitochondrial cytochrome C oxidase, and Atox1 to two trans -Golgi P1B-type ATPases (ATP7A and ATP7B) [13]. It has been reported that ZF domain is involved in nuclear targeting of Sp1 [14].…”
mentioning
confidence: 99%
“…Recent studies demonstrated that both CCS [32] and Atox1 [33] interact with hCtr1, suggesting a direct transfer of Cu +1 from hCtr1 to these carrier proteins (Figs. 1B & 1C).…”
Section: Mechanisms Of Cddp Transportmentioning
confidence: 99%